Immanuel Kant on Music: Paradoxes of Aesthetic Rationalism - Tatyana P. Razbeglova (Современные проблемы музыкознания)
The article explores the reasons behind the inconsistency of Kant's perspective on the art of music. Kant’s aesthetics is a strict and harmonious system underpinning the analysis of aesthetic consciousness. His views produced a huge impact on the subsequent development of aesthetic thought. Despite certain contradictions, the Kantian philosophical system and, in particular, his aesthetic views are of timeless value. In this respect, it is paramount to explore these contradictions and understand their role in the Kantian philosophy. Kant was repeatedly reproached for his formal approach to aesthetics that disregards artistic practice. However, it was not criticism but, rather, direct apologetics of Kant's philosophical vision promoted among his followers that led to aesthetic formalism. In other words, the rationality of thinking was transferred on the very object of exploration—the art. Kant's comments on music, as an integral part of his aesthetic theory, are formal and sparing. They contrast with a growing role of music in the cultural landscape at the turn of the 18th and 19th centuries and the scope of Kant’s commentary given to other arts. Nonetheless, the aesthetic value of music was still recognised as music was listed in Kant's classification of arts. Our research has concluded that the reasons behind Kant’s inconsistencies are not limited to the well-known gap between the aesthetic object and the judgment about it. Another reason is his conscious detachment from contemporary musical practice, and, more broadly, from the irrational essence of music which he implicitly felt. Kant's rejection of sensory and emotional perception of music in favor of its rational interpretation identified one of the key issues for the future research agenda in aesthetics. The question of whether it is possible to perceive music as a non-conceptual art with the help of rational thinking alone emerged from the contradictions of Kant's aesthetic. This issue has not lost its relevance. In fact, it has created the basis for modern transformations of musical art towards pronounced intellectualism. The identification of the essence and grounds for Kant’s contradictions will allow to fend off accusations of formalism put forward by his followers and critics.